Exploring the Predictive Role of 11‐Oxyandrogens in Diagnosing Polycystic Ovary Syndrome - Armaiti Parvez Mody; Maya Beth Lodish; Richard Joseph Auchus; Adina F. Turcu; Fei Jiang; Heather Gibson Huddleston (Endocrinology, Diabetes & Metabolism)
ABSTRACT Context Hyperandrogenism is a hallmark of polycystic ovary syndrome (PCOS), yet the androgen(s) responsible remain ambiguous. Recent studies have suggested that 11‐oxygenated C19 steroids (11‐oxyandrogens), specifically 11‐ketotestosterone, may be a good marker for hyperandrogenism in PCOS. Objective To investigate the utility of 11‐oxyandrogens to differentiate women with and without PCOS relative to classical androgens. Design Setting Case–control study performed at a PCOS clinic and research center in an academic setting. Patients 114 women with PCOS and 78 healthy controls. Interventions Using the PCOS Tissue Bank, serum samples and data from 114 women registered from 2013 to 2017 between the ages of 18–40 years, were obtained and classified using Rotterdam PCOS criteria. Data were compared to 78 healthy women of similar age, with serum samples obtained between 2017 and 2020. 11‐oxyandrogens and sex steroids were measured using mass spectrometry, and their associations to Rotterdam PCOS, age, and BMI were assessed. Main Outcome Measures 11‐oxyandrogens and sex steroids. Results Total testosterone, androstenedione, and four 11‐oxyandrogens were significantly elevated in women with PCOS compared to age matched controls, controlling for age and BMI (p < 0.01 for all). When considered together, the four 11‐oxyandrogens were more predictive of PCOS compared to testosterone and androstenedione. When all androgens were considered individually, 11‐ketoandrostenedione was the most predictive of PCOS. Of the six androgens studied, 11‐ketotestosterone was the only androgen that demonstrated a weak association with hirsutism score (r = 0.17; p = 0.07) within the PCOS group. Conclusion 11‐oxyandrogens were statistically higher in women with PCOS and may serve as better predictors of PCOS than testosterone and androstenedione.